The use of teat disinfectants and milking machine cleaning products in commercial Holstein-Friesian farms - Ózsvári, László; Ivanyos, Dorottya (Frontiers in Veterinary Science, 2022)
The aim of our study was to survey and analyze the use of pre- and post-milking teat disinfectants and milking machine cleaning products in large commercial Holstein-Friesian farms. A total of 43 Hungarian dairy farms with 31,430 cows with an average herd size of 731 cows was surveyed in 2014 by using a questionnaire via personal interviews. In the statistical analysis we used ANOVA models and Tukey’s multiple comparison method. Furthermore, seven in-depth individual interviews were conducted with farm managers. The results showed that 83.7% of the farms used different pre-milking disinfection methods (65.1% teat dips) and all of them applied post-milking disinfection. In the herds chlorhexidine (42.9%) and other chlorine (21.4%) compounds were the most widely used active ingredients in the pre-milking disinfection, while iodine in the post-milking disinfection (53.8%). Lactic acid was ranked second in both disinfections (25.0% vs. 41.0%) In post-milking teat disinfection the use of iodine and lactic acid combined with other active ingredients showed significant relationship with SCC (p = 0.0454; p = 0.0113). In the milking machine cleaning process, the most frequently used active ingredients were sodium hypochlorite (80.0%) and sodium hydroxide (60.0%) as caustic detergents, while phosphoric acid (81.3%) as acidic product. Significant relationship was found between the use of phosphoric acid combined with nitric acid, and the use of combination of phosphoric acid, nitric acid and organic acid and SCC (p = 0.0483; p = 0.0477). For farm decision-makers the most decisive factor in the procurement of teat disinfectants was the active ingredient (3.4 on a scale of 1 to 10 where 1 was the most important), while regarding milking machine cleaning products the price (3.2).